A Mendelian analysis of the relationships between immune cells and breast cancer - Wang, Xin; Gao, Haoyu; Zeng, Yiyao; Chen, Jie (Frontiers in Oncology, 2024)
Emerging evidence showed immune cells were associated with the development of breast cancer. Nonetheless, the causal link between them remains uncertain. Consequently, the objective of this study was to investigate the causal connection between immune traits and the likelihood of developing breast cancer. Methods A two-sample Mendelian randomization (MR) analysis was conducted to establish the causal relationship between immune cells and breast cancer in this study. Utilizing publicly accessible genetic data, we investigated causal connections between 731 immune cells and the occurrence of breast cancer. The primary approach for exploring this relationship was the application of the inverse-variance-weighted (IVW) method. Furthermore, sensitivity analyses, encompassing the leave-one-out analysis, Cochran Q test, and Egger intercept test were performed to validate the reliability of the Mendelian randomization results. Finally, we used Bayesian Weighted Mendelian Randomization (BWMR) approach to test the results of MR study.According to the Bonferroni correction, no immune trait was identified with a decreased or increased risk of overall breast cancer risk. As for the ER+ breast cancer, 6 immune trait was identified after the Bonferroni method. the IVW method results showed that CD45RA-CD4+ %CD4+ (p-value:1.37×10 -6 ), CD8dim %T cell (pvalue:4.62×10 -43 ), BAFF-R on IgD+ CD38-unsw mem (p-value:6.93×10 -5 ), CD27 on PB/PC (p-value:2.72×10 -18 ) lowered the risk of breast cancer. However, CD19 on IgD-CD38br (p-value:1.64×10 -6 ), CD25 on IgD+ CD38dim (p-value: -∞) were associated with a higher risk of developing breast cancer. As for the CX3CR1 on CD14+ CD16-monocyte (p-value: 1.15×10 -166 ), the IVW method clearly demonstrated a protective effect against ER-breast cancer. For the above positive results, BAFF-R on IgD+ CD38-unsw mem was the sole association linked to reduced breast cancer risk using the BWMR method. The intercept terms' p-values in MR-Egger regression all exceeded 0.05, indicating the absence of potential horizontal pleiotropy.Through genetic approaches, our study has illustrated the distinct correlation between immune cells and breast cancer, potentially paving the way for earlier diagnosis and more efficient treatment alternatives.